Effectiveness Trial of a Selective Dissonance-based Eating Disorder Prevention Program with Female College Students: Effects at 2- and 3-Year Follow-up - Stice, Eric (Behav Res Ther, 2015)
OBJECTIVE: An efficacy trial found that a dissonance-based prevention program reduced risk factors, eating disorder symptoms, and future eating disorder onset, but smaller effects emerged when high school clinicians recruited students and delivered the program under real-world conditions in an effectiveness trial. The current report describes results at 2- and 3-year follow-up from an effectiveness trial that tested whether a new enhanced dissonance version of this program produced larger effects when college clinicians recruit students and deliver the intervention using improved train and supervision procedures. METHOD: Young women from eight universities (N = 408, M age = 21.6, SD = 5.64) were randomized to the prevention program or an educational brochure control condition. RESULTS: Dissonance participants showed greater decreases in risk factors, eating disorder symptoms, and psychosocial impairment by 3-year follow-up than controls, but not healthcare utilization, BMI, or eating disorder onset. CONCLUSIONS: This novel multisite effectiveness trial found that the enhanced dissonance intervention and improved training and supervision procedures produced an average effect size at 3-year follow-up that was 290% and 160% larger than effects observed in the high school effectiveness trial and efficacy trial respectively. Yet, the lack of eating disorder onset effects may imply that factors beyond pursuit of the thin ideal now contribute to eating disorder onset.